Construction of Sea Barriers in Tangerang Based on Agrarian Law Perspectives and Implementation Issues - Muhammad Arasy Al Haq; Wardani Rizkianti (KRTHA BHAYANGKARA, 2025)
The issuance of hundreds of Building Use Rights certificates in the Tangerang sea area raises fundamental questions about the application of agrarian law in coastal areas, which should be public domain. This study analyze agrarian law aspects implementing problems sea wall construction in Tangerang, particularly regarding the legality of issuing HGB certificates in the sea area and their impact on the rights of coastal communities. The research method used is normative juridical. The results show that the issuance of 263 SHGB and 17 SHM in the sea area is contrary to UUPA Number 5 of 1960 because the sea area is not an object of land rights, thus containing juridical defects in terms of authority, procedure, and substance. The construction of the sea fence has violated the constitutional rights of coastal communities to work, a healthy environment, and fair legal certainty, causing significant economic losses in the form of increased operational costs for fishermen and the loss of traditional access to the sea. The problems in implementation reflect a failure of coordination between government agencies, a lack of synchronization of authority between the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), the Ministry of Marine Affairs and Fisheries (KKP), and the Investment Coordinating Board (BKPM) after the Job Creation Law, as well as construction without the mandatory Marine Spatial Utilization Conformity, which can be categorized as an unlawful act that violates the principle of state control for the prosperity of the people